Navicular stress fractures in identical twin runners - Murray, S. R.; Reeder, M.; Ward, T.; Udermann, B. E. (The Physician and Sportsmedicine, 2005)
Tarsal navicular fractures require an accurate and timely diagnosis to prevent costly and disabling complications. Diagnosis requires a thorough clinical evaluation that focuses on the patient's history, particularly his or her training regimen, and diet—as was the case with these 17-year-old girls. Plain radiography, ultrasound, bone scintigraphy, MRI, and CT help make a definitive diagnosis. Treatment of low-risk fractures involves relative rest and cessation of the precipitating activity. High-risk fractures often require non-weight-bearing immobilization, coupled with therapy, and may require surgery.